Partisipasi Masyarakat Gampong Tgk Dilaweung terhadap Pelestarian Terumbu Karang di Kecamatan Muara Tiga Kabupaten Pidie - Novia Zalmita; Muhammad Hafizul Furqan; Zul Usrati (Geography Education Study Program, Universitas Samudra, 2020)
The existence of coral reefs really helps the lives of people around the coast, such as the village of Tgk Dilaweung which is located in the coastal area. The purpose of this study was to determine the participation of the community in Gampong Tgk Dilaweung towards the preservation of coral reefs in Muara Tiga sub-district, Pidie district. To achieve this goal, 30 respondents were selected from the Gampong Tgk Dilaweung community around the coast using purposive sampling technique. This research uses descriptive analysis method to describe the community participation of Gampong Tgk Dilaweung towards the preservation of coral reefs. The data was collected by distributing questionnaires to respondents based on Arnstein's eight ladder of participation so that they can be categorized into 2 levels of participation, namely high, medium and low. From the results of data processing, it was found that all participation indicators given to 30 respondents were in medium and high positions. The highest percentage is in consultation resistance (87.8%) and is in the high category, while the lowest percentage is in the therapy and delegation stages of power (70%) but is still in the moderate category. Based on these data, it was concluded that the people of Gampong Tgk Dilaweung participated in protecting the coral reefs in the area.